2016
DOI: 10.1086/683666
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence and Divorce Law: When Divorce Threats Become Credible

Abstract: This paper investigates whether lowering the cost of divorce can reduce domestic violence. The cost of divorce influences the bargaining position of spouses, and thus, their behavior within the marriage. This study takes advantage of a large and unexpected reform of the divorce regime in Spain, which allowed for unilateral and no-fault divorce, and eliminated the pre-existing 1-year mandatory separation period, to estimate the causal effects. This reform dramatically reduced the cost of exiting a partnership f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Findings reported by a number of sociologists and economists indicate that one of the significant effects of the implementation of conflict-resolving no-fault unilateral divorce laws in the United States and Europe was a significant decrease in spousal femicides (husbands killing wives; Brassiolo, 2011;Dee, 2003;Dugan, Nagin, & Rosenfeld, 1999;Gillis, 1996;Stevenson & Wolfers, 1999). Economists identified the mechanism underlying the decrease as a "lowering of credible threat points" for leaving a relationship in which wives were being battered by husbands who may also have uttered death threats (Dee, 2003, p. 166).…”
Section: Introductionmentioning
confidence: 99%
“…Findings reported by a number of sociologists and economists indicate that one of the significant effects of the implementation of conflict-resolving no-fault unilateral divorce laws in the United States and Europe was a significant decrease in spousal femicides (husbands killing wives; Brassiolo, 2011;Dee, 2003;Dugan, Nagin, & Rosenfeld, 1999;Gillis, 1996;Stevenson & Wolfers, 1999). Economists identified the mechanism underlying the decrease as a "lowering of credible threat points" for leaving a relationship in which wives were being battered by husbands who may also have uttered death threats (Dee, 2003, p. 166).…”
Section: Introductionmentioning
confidence: 99%
“…A national survey that listened to 19 women revealed that the partner's infidelity incites conflicts between the couple, as women tend to question such behavior, which generates conjugal violence (36) . A study carried out in Spain also found that most cases of conjugal violence are motivated by male betrayal, and when the woman decides to separate, she also begins to suffer threats and even situations of physical violence (39) . Thus, when they are betrayed, women are more likely to suffer violence, either because they protest or because they decide to separate, and it is up to them to ensure their protection, only to accept the betrayal without question.…”
Section: Discussionmentioning
confidence: 99%
“…Estimations include individual level controls, and country and year fixed effects. ;2005, 20142005, 20142007, 2013, 2014Cameroon, 20112007, 2013Colombia 2004, 2005, 2009, 20102012 Democratic Republic of Congo;2007, 2013, 20142008 Dominican Republic;2007, 201320052012 Honduras;2008 India;200520052008, 2009, 20142012 India;2005, 2007Jordan, 20072010, 2015, 20162008, 2009, 2014, 20132012 Mozambique;2011 Liberia;, 200720102010, 2015, 2016…”
Section: Supplementary Appendixmentioning
confidence: 99%